Evolution of acute chest syndrome in sickle cell trait: an ultrastructural and light microscopic study. Issue 12 (December 1989) - Hasleton, P S; Orr, K; Webster, A; Lawson, R A
Abstract : Light and electron microscopic studies of a patient with sickle cell trait who had an episode of sickling during coronary artery surgery, from which he died, showed fibrin thrombi, focal alveolar wall necrosis, and epithelial cell damage. It is suggested that in cases of sickle trait full precautionary measures should be taken to prevent sickling in these circumstances.